Bi‐Facial Substrates Enabled Heterogeneous Multi‐Dimensional Integrated Circuits (MD‐IC) for Internet of Things (IoT) Applications. Issue 7 (10th April 2019) - El‐Atab, Nazek; Shaikh, Sohail F.; Khan, Sherjeel M.; Hussain, Muhammad M.
Abstract : The primary focus of modern electronics technology is to increase its functionalities within a smaller footprint at an affordable cost. This creates a new set of design challenges for the already‐existing complex integration and packaging schemes. Here, CMOS‐compatible and heterogeneous multi‐dimensional integrated circuits (MD‐IC) as smart electronic systems for Internet of Things (IoT) applications are shown. Both sides of bulk monocrystalline Si (100) substrate for device fabrication which are connected via through‐silicon‐via to transform it into bi‐facial CMOS electronics system are used. As a proof‐of‐concept, cubic, pyramidal, and buckyball shaped MD‐ICs, with broad variety of devices including humidity, temperature, pressure, and pH sensors, solar cells, antenna, microcontroller, light emitting diode and micro lithium‐ion battery are shown. In these MD‐ICs, adjacent sides are interconnected through side‐interlocks. It is also shown that polymeric encapsulation and heterogeneous materials (Si, Ge, and GaSb) can be integrated in the MD‐IC architecture to meet the rigorous requirements of IoT devices. Compared to folded rigid or flexible Printed Circuit Board based electronics, this report shows unprecedented usage of area by device fabrication on both sides which are also connected through‐silicon‐via as state‐of‐the‐art tool for 3D‐IC manufacturing. Abstract : In this work, we introduce the concept of multi‐dimensional integrated‐circuits (MD‐IC) which combines between the best of the existing integration and packaging technologies. MD‐IC is based on the integration of thin‐film components and provides a complete, multi‐functional, lightweight, high‐performance and compact‐packaged system. A working prototype for IoT applications has been demonstrated with microcontroller, sensors, solar cell, battery, antenna and LED.